Atividades enzimáticas da celulase, cinéticas e modelagem matemática da decomposição das macrófitas emergentes Hedychium coronarium J König e Typha domingensis Pers - Paccagnella, Yeda Carolina (Universidade Federal de São Carlos, 2017)
The decomposition of a single macrophyte species may not represent entirely the carbon cycling in aquatic ecosystems, once in these environments several species growth and decay concomitantly. To describe the interaction of decomposition, the temporal variation of particulate organic carbon (POC) of Hedychium coronarium, Typha domingensis and the mixed samples (50% of each species) of these macrophytes were analyzed. Kinetic models were used to verify the temperature and the availability of dissolved oxygen, as regulation factors for the in vitro decomposition. Decomposition bioassays were prepared with dry plant fragments and water samples from the Fazzari Reservoir (47 o 53 ́ 15.80 ́ ́W and 21 o 58 ́ 15.19 ́ ́S). The incubations were maintained under aerobic and anaerobic conditions at 15, 20, 25 and 30 o C. From the chemical point of view, the detritus (single plants and the mixed samples) presented heterogeneous characteristics. The mean values of the labile fraction decay coefficients (k LS ) and the refractory fraction (k R ) of POC were parameterized. The POC temporal variation decay of H. coronarium (Treatment I), T. domingensis (Treatment II) and mixed litters (Treatment III) allowed to observe that, in general, aerobic processes favored the faster POC decay. The increasing temperature influenced the POC loss of mass in the three treatments (I: H. coronarium, II: T. domingensis and III: mixed samples). The Q 10 values in aerobiosis were 1.46, 1.55 and 2.00, and in anaerobiosis were 1.03, 1.26 and 2.09, for Treatments I, II and III, respectively. The anaerobic processes presented higher dissolved organic carbon (DOC) yields than the aerobic. The detritus decay in the Treatments I, II and III was % higher in the aerobic conditions. In general, a trend of pH increases during aerobic and anaerobic decomposition processes was observed. Among the 3 treatments, the mixed samples presented lower electrical conductivity values at 15, 20 and 30 o C, in which T. domingensis presented the highest values, however at 25 o C, the highest values were observed for H. coronarium. A tendency of increased enzymatic activity was observed in H. coronarium (aerobic and anaerobic conditions) and in mixed litters (aerobic conditions) as the temperature increases. The average phosphorus content of the remaining POC found in the aerobic and anaerobic incubations of H. coronarium showed the highest values among the 3 treatments, and T. domingensis litters presented intermediate values, as the temperature increased. The highest phosphorus content was found in mixed litters incubations under anaerobic conditions at 30°C. Interactive responses were evaluated in the mixed litter decomposition. Extrinsic factors (i.e. temperature and dissolved oxygen) and the chemical plants composition influenced the mixed samples decomposition processes, being observed antagonistic effects in aerobic incubations, at all temperatures, and, in anaerobic conditions, antagonistic (15 o C), additive (20 and 25 o C) and synergistic effects (30°C) were observed.
Cellulase enzymatic activities, modeling mathematics and kinetics decomposition of emergent macrophytes Hedychium coronarium J König and Typha domingensis Pers
Keywords: Carbono orgânico particulado; Carbono orgânico dissolvido; Mistura de detritos; Modelo cinético; Condições aeróbias; Condições anaeróbias; Efeito de temperatura; Q 10; Respostas Interativas; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS